Психофеноменологический профиль в психотерапевтическом диагнозе (типология и психотехническая конгруэнтность) = Psychophenomenological profile in psychotherapeutic diagnosis (types and psychotechnichnical congruence) - Zasieda, Uy. I. (Journal of Education, Health and Sport, 2015)
Zasieda Uy. I. Психофеноменологический профиль в психотерапевтическом диагнозе (типология и психотехническая конгруэнтность) = Psychophenomenological profile in psychotherapeutic diagnosis (types and psychotechnichnical congruence). Journal of Education, Health and Sport. 2015;5(11):300-310. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34027 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A300-310 https://pbn.nauka.gov.pl/works/670468 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 10.11.2015. ПСИХОФЕНОМЕНОЛОГИЧЕСКИЙ ПРОФИЛЬ В ПСИХОТЕРАПЕВТИЧЕСКОМ ДИАГНОЗЕ (ТИПОЛОГИЯ И ПСИХОТЕХНИЧЕСКАЯ КОНГРУЭНТНОСТЬ) PSYCHOPHENOMENOLOGICAL PROFILE IN PSYCHOTHERAPEUTIC DIAGNOSIS (TYPES AND PSYCHOTECHNICHNICAL CONGRUENCE) Ю. И. Заседа Uy. I. Zasieda Харьковская медицинская академия постдипломного образования, Харьков Украина Kharkov Medical Academy for Advanced Training of Doctors, Kharkov, Ukraine Summary The formation of a typology of data of psychophenomenological profile and develop of a methodology of denotating of them into structure of psychotherapeutic diagnosis is an urgent problem in the context of clinical-disciplinary design psychotherapy. In order to develop a methodology of the selection of congruent psychotechnical support and mechanism of its incorporating into the structure of psychotherapeutic diagnosis based on the analysis of variability of data of psychophenomenological profile in patients suffering from the most common forms of somatoform disorders and psychosomatic diseases were examined 400 patients using clinically-psychophenomenological, clinically-anamnestic, clinically-psychopathological, clinically-psychodiagnostic and statistical methods. As the result of a study idiographic aspect of the psychophenomenological profile as a module of personalization of systems of psychotherapy and psychophenomenological component of psychotherapeutic diagnosis is designed, consisting of complementary descriptions of psychotechnical assurance and recommended clinical psychotherapeutic effect-syndrome. Keywords: psychophenomenological profile, clinically- psychophenomenological method, somatoform disorders, psychosomatic illnesses. Реферат Формирование типологии данных психофеноменологического профиля и разработка методологии их денотации в структуру психотерапевтического диагноза является актуальной проблемой в контексте клинико-дисциплинарного оформления психотерапии. С целью разработки методологии селекции конгруэнтного психотехнического обеспечения и механизма вконструирования в структуру психотерапевтического диагноза на основании анализа вариабельности данных психофеноменологического профиля у пациентов, страдающих наиболее распространенными формами соматоформных расстройств и психосоматических заболеваний было обследовано 400 пациентов с помощью клинико-психофеноменологического, клинико-анамнестического, клинико-психопатологического, психодиагностического и клинико-статистического методов. В результате исследования разработан идиографический аспект психофеноменологического профиля в качестве модуля персонализации процесса психотерапии и разработана психофеноменологическая составляющая психотерапевтического диагноза, состоящая из комплементарного описания психотехнического обеспечения и рекомендованного клинического психотерапевтического эффект-синдрома. Ключевые слова: психофеноменологический профиль, клинико-психофеноменологический метод, соматоформные расстройства, психосоматические заболевания.